Clinical manifestations associated with the chronic phase of Chikungunya Fever: A systematic review of prevalence. - Raphael Augusto Santiago; Suelen Pereira Priante Bavaresco; Sheyla Goulart Citrangulo; Roberto de Andrade Medronho; Vanderson Sampaio; Antônio José Leal Costa (PLoS Neglected Tropical Diseases)
Introduction The aim of this systematic review of prevalence is to observe and discuss the clinical manifestations of Chikungunya Virus disease in its chronic phase. Methods To be eligible, the observational studies should accompany the individuals for at least six months. The research was conducted using electronic databases MEDLINE and EMBASE. The methodological quality was evaluated using the "Joanna Briggs Institute's critical appraisal checklist for studies reporting prevalence data" tool. Results The search has found 175 articles. The application of the inclusion criteria defined a total of 29 selected studies. From the included studies, only one did not present arthralgia as a prevalent symptom in the chronic phase. Other signs and symptoms observed were: fatigue; sleep disorders; myalgia; skin lesions; depression; digestive disorders. Conclusion Because it is an often incapacitating symptom, arthralgia can affect the individuals' quality of life, with implications in their social and work life. Since the chronic phase is common in infected individuals, all levels of health care should be prepared to monitor, in the medium to long term, the patients affected by this condition.